Lateral spread evolving from a deep-seated gravitational slope deformations to the front of the apenninic-maghrebian chain (southern sicily) - Ferrara, Vincenzo; Pappalardo, Giovanna; Rapisarda, Francesco (Italian journal of engineering geology and environment, 2008)
The work examines the evolution of a lateral spread located in the southern coast of Sicily. The geological-structural framework of the area is represented by the Plio-Pleistocene Gela Nappe, the most advanced deformational front of the Apenninic-Maghrebian Chain in southern Sicily. The recent uplift of the area has increased the relief energy and the lithostructural conditions of the slopes where rigid rock overlie material with plastic behaviour, causing the activation of lateral spreading evolving from a Deep Seated Gravitational Slope Deformation (DGSD). Geological and morphological analyses allowed the detailed reconstruction of the movement mechanism of the phenomena in the study area. DGSD induce slow landsliding movements whose effects are par- ticularly evident in man-made structures such as roads and buildings.